2022
DOI: 10.1038/s41467-022-29754-y
|View full text |Cite
|
Sign up to set email alerts
|

DENR controls JAK2 translation to induce PD-L1 expression for tumor immune evasion

Abstract: RNA-binding proteins (RBPs) can recognize thousands of RNAs that help to maintain cell homeostasis, and RBP dysfunction is frequently observed in various cancers. However, whether specific RBPs are involved in tumor immune evasion by regulating programmed death ligand-1 (PD-L1) is unclear. Here, we perform targeted RBP CRISPR/Cas9 screening and identify density regulated re-initiation and release factor (DENR) as a PD-L1 regulator. DENR-depleted cancer cells exhibit reduced PD-L1 expression in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…5,20,21 JAKs have also been shown to increase expression of checkpoint proteins, including PD-L1. 27 BM from MM patients with PD shows increased expression of this protein and also the checkpoint protein B7H3. 13,15,16 Moreover, ruxolitinib blocks expression of these checkpoint proteins and increases anti-tumour T-cell activity in MM BM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,20,21 JAKs have also been shown to increase expression of checkpoint proteins, including PD-L1. 27 BM from MM patients with PD shows increased expression of this protein and also the checkpoint protein B7H3. 13,15,16 Moreover, ruxolitinib blocks expression of these checkpoint proteins and increases anti-tumour T-cell activity in MM BM.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that JAK inhibitors have anti‐inflammatory effects that have led to their effective use to treat a variety of auto‐immune diseases, graft‐versus‐host disease and severe COVID‐19 infection 5,20,21 . JAKs have also been shown to increase expression of checkpoint proteins, including PD‐L1 27 . BM from MM patients with PD shows increased expression of this protein and also the checkpoint protein B7H3 13,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is highly expressed in several cancer types [ 56 ] and much more in TNBCs compared with other breast cancer subtypes [ 57 ]. Genetic and epigenetic mechanisms, as well as inflammatory stimuli, control PD-L1 expression in cancers [ 58 , 59 ]. We demonstrated that IL-3Rα activation increases PD-L1 expression in primary tumours and in metastatic lung lesions, sustaining a role in the control of anti-tumour immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells possess abundant PD-L1, which binds to the PD-1 receptor on the surface of tumor-infiltrating lymphocytes (TILs), subsequently sending immunosuppressive signals to TILs and preventing antigen-specific CD8 + T lymphocytes from eliminating tumor cells [ 13 16 ]. Moreover, PD-L1 enables the promotion of tumor therapy through non-T cell-mediated immunity.…”
Section: The Expression and Biological Function Of Pd-l1mentioning
confidence: 99%
“…PD-L1 upregulation occurs across a broad spectrum of cell types as a result of stimulation by proinflammatory cytokines and other factors, and PD-L1 is highly expressed in many cancer cells such as lung, ovarian, colon, and melanoma [11,12]. Tumor cells possess abundant PD-L1, which binds to the PD-1 receptor on the surface of tumor-infiltrating lymphocytes (TILs), subsequently sending immunosuppressive signals to TILs and preventing antigen-specific CD8 + T lymphocytes from eliminating tumor cells [13][14][15][16]. Moreover, PD-L1 enables the promotion of tumor therapy through non-T cell-mediated immunity.…”
Section: The Expression and Biological Function Of Pd-l1mentioning
confidence: 99%